New data fusion model of intrusion detection——IDSFP - TIAN Jun-feng; ZHAO Wei-dong; DU Rui-zhong; CAI Hong-yun (Tongxin xuebao)
Based on multi-sensor data fusion technology,a new intrusion detection data fusion model-IDSFP was pre-sented.The model was characterized by correlating and merging alerts of different types of IDS,generating the measures of the security situation,thus constituting the evidence.Current security situation of network was evaluated by applying the D-S evidence theory,and various IDS of network were adjusted dynamically to strengthen the detection of the data which relates to the attack attempt.Consequently,the false positive rate and the false negative rate are effectively reduced,and the detection efficiency of IDS is accordingly improved.